Power-efficient high fidelity analog audio class D amplifiers - Sun, Huaxi (2014)
Class D amplifiers are increasingly prevalent in audio applications due to its high power-efficiency. Conventional power amplifiers like Class A, Class B and Class AB amplifiers have certain limitation in maximum power-efficiency and conventional silicon output stage transistors may not satisfy the requirements of extremely high efficiency and high speed applications. This Final Year Project aims to use GaN power transistors as the output stage to achieve better performance than silicon transistors. The physical properties of GaN transistors enable them to feature low resistance when operating in triode region and fast transition during switching in Class D configuration. Since the research results of GaN transistors are not sufficient at present, the author mainly targets to build up a Class D system which could be used to verify the properties of GaN transistors.